Pengembangan Ludo Kimia berbasis Chemo-Edutainment (CET) sebagai Media Pembelajaran pada Materi Sistem Koloid Kelas XI SMA/MA - Febriyeni, Rahma (RC-INSTITUT, 2019)
This research aimed to produce Chemistry Ludo base on Chemo-Edutainment (CET) as a Learning Media on Colloid System Chemical for class XI SMA/MA and determined the validity and practicalty of this media. The type of this research was Research and Development (R&D) with a 4-D models, (1) define, (2) design, (3) develope, and (4) disseminate. This media was validated by three lecturers of Kimia FMIPA UNP and two chemistry teachers at SMAN 7 Padang. Determination of the practicality was carried out by two chemistry teachers at SMAN 7 Padang and 30 students XII IPA 4 at SMAN 7 Padang. The instrumen used were  questionnaire validity and practicality. Data collection techniques were carried out by distributing questionnaires and analized using the Cohen Kappa formula. From the data analysis, it was found that  Chemistry ludo based on CET had validity 0,81 with a very high validity category. The practicality by teachers and students was  0,99 and 0,92 with very high practicality categories. This data shows that Chemistry Ludo base on CET developed can be used as a learning media on Colloid System for class XI SMA/MA.